I.i. Title deeds and related papers, - Cuffe, Joseph, 1621-1679; Grattan Bellew family; Cosby, Richard, 1576-1631 (1609)
Deeds concerning Stradbally, Cuffsboro (Queen's County), Desart, Cuffe's Grove, Castleinch (Co. Kilkenny, at the border with the Laois estates).